Tingkat Keterampilan Senam Lantai Guling Depan Pada Siswa Sekolah Dasar - Prasetyo, Guntum Budi; Ahmad, Nurdian (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of the study was to see the level of floor gymnastics ability in the front roll of students. The research method uses a quantitative descriptive approach and the type of research with the survey method, sampling with purposive sampling with a sample size of 82 students. Research instruments with front roll skill tests and data analysis with descriptive statistics with percentages. The results of the research on the level of front rolling skills in the excellent category (0%), good (15.86%), moderate category (43.90%) less (20.73%), and very poor category (19.51%). The conclusion in the study can be understood that the front roll skills of students who are in the moderate category.